Ayurvedic Treatment Regime of Hypomenorrhea w.s.r. to Alpartava : A Case Study - Kumari, Monika; Bansal, Jitesh; Khathuria, Diksha; Joshi, Kushwant (International Research Journal of Ayurveda & Yoga, 2022)
Background: Hypomenorrhea is a menstrual condition where menstrual cycle is disturbed due to various factors. Hormonal imbalance, stress, local cause, defect in H- P-O axis etc can lead to any menstrual deformity. At the beginning of hypomenorrhea, treatment should be started so that it can be resolved easily and in short period of time. Ayurvedic treatment can be done to treat the condition. For this condition also, treatment should be done with a aim to normalize the vitiated Dosha and Dhatu. Scanty Artava is seen in this condition and treatment is done for increasing Artava. Main observations: In present study a 25-year-old women patient consulted the Ayurvedic OPD of M.M.M. Govt. Ayurved College& Hospital, Udaipur with the complaint of scanty menses lasting for 1 or 2 days with normal interval of menstrual cycle. So, we planned an Ayurvedic treatment regime with the goal of improving the symptoms of patient. Result: This patient was treated with ayurvedic formulations like Chandranshu ras, shatavari ghrita, chaturbeej churna. Syrup Evecare forte. Only traditional Ayurvedic medicines were used during the treatment. This case study demonstrates the efficacy of Ayurvedic treatment for Urticaria. So, Patient’s condition was assessed through improvement in symptoms. Therefore, this study was conducted to evaluate one of the treatment regimens for hypomenorrhea. Conclusions: The study reached the conclusion that ayurvedic treatment was significantly effective in the treatment of Alpartava (Hypomenorrhea).